AB0713 Comparison of icg-enhanced fluorescence optical imaging and musculoskeletal ultrasound in patients with rheumatoid arthritis and osteoarthritis. (23rd January 2014) - Glimm, A.-M.; Werner, S. G.; Ohrndorf, S.; Schwenke, C.; Schmittat, G.; Burmester, G. R.; Backhaus, M.
Abstract : Background: The pathological modification of Rheumatoid arthritis begins with synovitis as an inflammatory process early in the course of disease. Withal synovitis is accompanied with hypervascularisation and neoangiogenesis which can be visualized by the new ICG-enhanced fluorescence optical imaging (FOI). Objectives: To compare (FOI) and musculoskeletal ultrasound (US) in patients with rheumatoid arthritis (RA) und osteoarthritis (OA). Methods: Grey-scale (GSUS) and power Doppler (PDUS) ultrasound were applied on dorsal and palmar sides of wrists, MCP- 2-5, PIP- 2-5 and DIP – joints 2-5 of the clinically more affected hand of 90 patients (67 RA, 23 OA). FOI was performed following the usual procedure [1 ]. Synovitis, tenosynovitis on ultrasound and the ICG distribution on FOI were graded by a semiquantitative score (0-3) and on a qualitative (0/1) basis. For the statistical analysis, sensitivity and specificity for each GSUS and PDUS with synovitis or tenosynovitis, palmar or dorsal side as reference were calculated. Results: Depending on the considered phase, sensitivity and specificity for both RA and OA show a moderate range. The sensitivity for the prima vista mode (PVM) in RA with GSUS as reference is 50%, with PDUS 62%. In the phases the sensitivity for RA and GSUS as reference assumes values between 25% and 68%. The sensitivity range for PDUS is on a higher level between 30% and 77%. The highest level can be seen in phase 2 with 68% for GSUS and 77% for PDUS. Regarding the PVM, the specificity for GSUS is 93% and for PDUS 85%. The value ranges in the phases for GSUS are between 78% and 96%, for PDUS between 74% and 90%. The highest levels for specificity were reached in phase 3. For OA, the GSUS sensitivity level for the PVM is 63%. For PDUS as reference the sensitivity adopts a value of 69%. Considering the phases the sensitivity ranges for GSUS between 19% and 77% and for PDUS between 31% and 89%. The highest level is also reached in phase 2. The specificity for PVM in OA is 79% for GSUS and 77% for PDUS. In the phases it takes a range between 69% and 88% with GSUS as reference. Concerning PDUS, the specificity ranges between 69% and 88%. Also here, the highest levels can be found in phase 3. Conclusions: Thus sensitivity and specificity in both considered cohorts OA and RA show similar ranges of values, the method can detect inflammatory activity regardless of the diagnosis. The highest sensitivity values were found for phase 2 in both diseases. Therefore, reliable differentiation of the individual diagnoses regarding to the different phases on basis of the performed statistical calculations cannot be made in this study. These results differ from other studies [1 ] which might be due to the investigator dependence of both ultrasound and FOI. To limit the investigator dependence, further standardization of the evaluation criteria should follow. References: Werner SG, Langer H-E*, Ohrndorf S*, et al. *equal contribution: Inflammation assessment in patients with arthritis a novel in vivo fluorescence optical imaging technology. Ann Rheum Dis 2012;71:504-5010. Disclosure of Interest: None Declared